The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14502/tekstilec2015.58.191-198
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mordanting with Silver Nitrate on the Dyeability and UV Protection of Cotton Dyed with Green Tea

Abstract: Silver nitrate (AgNO 3 ) was used as a mordant for dyeing cotton fabric with natural dyes. Due to the high concentrations of catechin and tannin, green tea was used as a natural dye. The green tea extraction was performed under neutral and alkaline conditions. Four molar concentrations of AgNO 3 were used, namely 1, 5, 10 and 50 mM. Mordanting was performed during dyeing with green tea extracts. The colour (CIE L*a*b* values) and UV protection factor (UPF) of the dyed cotton samples before and after ten repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Catechin is one of the natural phenols and antioxidants [11]. Due to antioxidant and deodorization functions on natural bres, many researches were carried out using green tea as a dye [12]. It was found that hot extraction of red, black and green tea provided cotton fabrics with UVblocking properties [13].…”
Section: Green Teamentioning
confidence: 99%
“…Catechin is one of the natural phenols and antioxidants [11]. Due to antioxidant and deodorization functions on natural bres, many researches were carried out using green tea as a dye [12]. It was found that hot extraction of red, black and green tea provided cotton fabrics with UVblocking properties [13].…”
Section: Green Teamentioning
confidence: 99%